Effects of Lime-Cement Column Characteristics on the Performance of an Embankment on Soft Clay - An Analysis Using Volume Averaging Technique in Plaxis 2D - OLOFSSON HOFFMANN, Kristin; HÖJER, Elin (My University, 2022)
Lime-cement columns are commonly used in Sweden as a ground improvement method. In this thesis a system consisting of an embankment on lime-cement columns is studied. The aim of the study is to investigate the impact of limecement column characteristics on the stress-strain response of the described system. It is also investigated how well the use of column guideline values from Trafikverket complies with the stress strain response of lime-cement columns measured in field. The embankment, located in Nödinge north of Gothenburg, is a former full-scale test embankment part of a feasibility study for the development of a new motorway and high-speed railway. When modelling lime-cement columns under an embankment a full 3D analysis is needed, something which is both time consuming and complicated to conduct. Thus, in this thesis the system was modelled using the Volume Averaging Technique (VAT) in Plaxis 2D. The VAT-model implements two constitutive models, S-CLAY1S and MNhard, for the soil and the columns, respectively, and converts the 3D problem to a 2D problem. The study shows that an increased column stiffness leads to decreased settlements. However, the effect of the column stiffness on the deformation behaviour seems to lessen with increasing column stiffness. Furthermore, the predicted vertical displacements using a column stiffness corresponding to Trafikverket’s guideline values are significantly larger than those measured at the site. This indicates that the stiffness of the columns in Nödinge is much higher than the stiffness given by the guideline values. The results are further supported by laboratory tests on lime-cement column samples which also showed higher stiffnesses than the guidelines. However, the laboratory tests also exhibit a large span of stiffnesses. This suggests that it is necessary to have lower guidelines to account for the uncertainties regarding the column stiffness. Since cement is a large contributor to the world’s CO2-emissions, it is of great interest to lower the amount of stabiliser used. Therefore, further investigations on how well the guidelines coincides with the actual stiffness of lime-cement columns used in field, are suggested.
Keywords: Lime-Cement Columns; Settlements; Plaxis 2D; Embankment; S-CLAY1S; MNhard; Volume Averaging Technique